GNSS data processing strategies and antenna phase center calibration techniques - Abdalla, Meaad; Johansson, Frida (My University, 2022)
GNSS-related applications have increased dramatically in recent decades, raising the need for more precise results. Thus, enhancements for GNSS’s different segments are vital to achieving higher accuracy. The receiver-related biases are prominent errors that affect GNSS measurements and results, particularly errors associated with the antennas and their phase-center. In addition, identifying the correct antenna measuring point is difficult since phase-centers are electrical characteristics that change with frequency, elevation, and azimuth angles. Therefore, antenna calibration is indispensable to mitigate phase-center related errors. Multiple approaches are currently employed to calibrate GNSS antennas, specifically model-specific and antenna-specific. Although these techniques have consid erably contributed to GNSS accuracy, they face limitations related to the respective site specifications. Using the internationally available (ONSA & ONS1) and regional (OTT 1 through 6) GNSS stations at the Onsala Space Observatory (OSO), the impact of different calibra tion methods on GNSS accuracy has been investigated. Station-specific corrections were also considered in the study. Various constraints and cut-off elevation angles were exam ined and modified to reduce the influence of other error sources. Data from 2019 -2021 for GPS, Galileo, and GLONASS constellations, were collected and processed using the GipsyX v.1.7 software, which uses the Precise Point Positioning technique. During the processing, a period of 30 hours, instead of the typical 24 hours, of observations was used to guarantee higher stability for the Kalman filter. In addition to the coordinate estimations, the analysis included the tropospheric zenith delay (ZTD) and tropospheric gradients. The estimated delay parameters were verified and compared with estimations from other measurement techniques such as Very Long Baseline Interferometry (VLBI) and water vapor radiometer (WVR). Temporary stations were established at four accu rate geodetic checkpoints from March-May 2022 to be used to derive a station-specific calibration matrix for the international stations at OSO. It was found that supported by other measurement techniques, the examined constraints and elevation cut-off values im pact the accuracy of GNSS results. Model-specific calibration values were compared with VLBI & WVR results. However, minor differences were detected when comparing model and antenna-specific calibration methods.
Keywords: GNSS, Zenith Total Delay, Tropospheric Gradients, Antenna Phase-Center, GipsyX , GPS, Precise Point Positioning, Onsala Space Observatory